ANALISIS PERBANDINGAN EFISIENSI PROFITABILITAS BANK-BANK DI NEGARA-NEGARA ASEAN - Tsumma Lazuardini Imamia (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2015)
Key of facing competition in the AEC (ASEAN Economic Community) banks should improve the efficiency. To achieve maximum profit, bank must manage costs. By using Data Envelopmen anlaysis (DEA), this study measures the efficiency of profitability of banks in ASEAN-5 (Indonesia, Malaysia, the Philippines, Singapore, and Thailand) in 2011-2014. Input variables include interest expense and non-interest expense. Then the output is profit before tax. The results of this study indicate Singapore banks had an average score of the highest efficiency in the 2011-2014 period. Kruskal Wallis test results show there are differences in the average efficiency of Singapore banking with other countries.Keywords: AEC, Data Envelopmen anlaysis (DEA), profit efficiency, ASEAN-5